X-ray and morphological characterization of Al-O thin films used for vertically aligned carbon nanotube growth - Mohd Abid, Mohd Asyadi Azam; Mohd Warikh, Abd Rashid (Trans Tech Publications, 2013)
Al oxide (Al-O) films used as catalyst-support layer for vertical growth of carbon nanotubes (CNTs) were characterized by means of X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), transmission, and scanning electron microscopies (TEM and SEM). EB-deposited Al films (20 nm) were thermally-oxidized at 400 o C (10 min, static air) to produce the surface structure of Al-O. The Al-O was found amorphous and after the incorporation with Co catalyst, the grown CNTs were twisted together before vertically grown. The prepared Al-O surface is an electron-acceptor-dominated (oxygen-rich) surface where the formation of active catalyst could be enhanced to promote the vertically aligned CNT growth.